Burmese grape (Baccaurea ramiflora) of Tripura: A hidden gem of northeast India’s exotic fruit diversity - Bhattacharjee, Panchaal; Debbarma, Sajal (Indian Horticulture, 2025)
In the diverse landscape of Indian agriculture, one can find a myriad of fruits that tantalize the taste buds and reflect the country’s rich biodiversity. Among these, Burmese grape (Baccaurea ramiflora), an underutilized and underexploited valuable fruit crop, stands out as a lesser-known yet fascinating addition. Locally known as ‘Lotkon,’ ‘Bubi’ or ‘Kusumai,’ the Burmese grape has found a niche in Tripura, noteworthy for its abundant natural bioactive compounds that offer diverse health benefits. It is known for its sweet taste, juicy pulp, and high-water content. In Tripura, the Burmese grape holds significant economic, nutritional, and cultural value, playing a vital role in the region’s agricultural landscape.